2015
DOI: 10.3141/2525-12
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Pavement Surface Macrotexture and Friction

Abstract: The amount of available friction and texture depth are primary concerns in the evaluation of pavement surface safety characteristics. The two components of microtexture and macrotexture provide pavement surface friction. Macrotexture properties are collected with laser-based devices at highway speeds, but a proper evaluation of microtexture is available only with stationary devices or laboratory experimental methods. The industry is trying to develop practical methods for monitoring microtexture at the network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…These models were developed by using traditional texture indicator MTD and/or MPD for texture-friction relationship establishment. The obtained R 2 values vary from no significant correlation for simple models [26][27][28] to moderate or even strong correlation for models [21][22][23][24][25]. By observing the obtained R 2 values for complex models, it can be seen that they generally showed more consistency in friction prediction in comparison to simple models with only one or two predictors.…”
Section: Empirical Models Based On Traditional Texture Characterizationmentioning
confidence: 85%
See 2 more Smart Citations
“…These models were developed by using traditional texture indicator MTD and/or MPD for texture-friction relationship establishment. The obtained R 2 values vary from no significant correlation for simple models [26][27][28] to moderate or even strong correlation for models [21][22][23][24][25]. By observing the obtained R 2 values for complex models, it can be seen that they generally showed more consistency in friction prediction in comparison to simple models with only one or two predictors.…”
Section: Empirical Models Based On Traditional Texture Characterizationmentioning
confidence: 85%
“…Simple models [21][22][23][24][25][26][27] were derived from extensive pavement texture and friction measurements, performed by traditional measurement procedures defined in relevant European standards for texture measurements [5,8] and friction measurements [10,11]. Complex models [28][29][30][31][32] were derived in cases where influential parameters other than texture, such as friction measurement speed, environmental effects, and different dataset sizes, were considered in the model establishment.…”
Section: Empirical Models Based On Traditional Texture Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the relationship between the macro-texture and skid resistance performance, studies have demonstrated that the correlation between the anti-skidding performance and traditional macro-texture evaluation indexes, such as Mean Profile Depth (MPD) and Mean Texture Depth (MTD), remain to be discussed. However, in recent years, great progress has been made in the following aspects, namely, the data acquisition of the macroand micro-texture of pavement surface by high-precision and non-contact measurement methods, as well as their application in the investigation of the surface texture evolution and pavement anti-skidding performance prediction [16][17][18][19][20]. This contributes to the fast acquisition and precise characterization of surface texture.…”
Section: Introductionmentioning
confidence: 99%